The Effects of Different Roughness Configurations on Aerodynamic Performance of Wind Turbine Airfoil and Blade - Kamyar Jafari; Mohammad Hassan Djavareshkian; Behzad Forouzi Feshalami (International Journal of Renewable Energy Development, 2017)
In this research, viscous and turbulent flow is simulated numerically on an E387 airfoil as well as on a turbine blade. The main objective of this paper is to investigate various configurations of roughness to find a solution in order to mitigate roughness destructive impacts. Hence, the sand grain roughness is distributed uniformly along pressure side, suction side and both sides during the manufacturing process. Navier-Stokes equations are discretized by the finite volume method and are solved by SIMPLE algorithm. Results indicated that in contrast with previous studies, the roughness will be useful if it is applied on only pressure side of the airfoil. In this condition, the lift coefficient is increased to  and 1.2% compare to the airfoil with rough and smooth sides, respectively. However, in 3-D simulation, the lift coefficient of the blade with pressure surface roughness is less than smooth blade, but still its destructive impacts are much less than of both surfaces roughness and suction surfaces roughness. Therefore, it can be deduced that in order to reveal the influence of roughness, the simulation must be accomplished in three dimensions.Article History: Received Jun 12th 2017; Received in revised form August 27th 2017; Accepted Oct 3rd 2017; Available onlineHow to Cite This Article: Jafari, K., Djavareshkian, M.H., Feshalami, B.H. (2017) The Effects of Different Roughness Configurations on Aerodynamic Performance of Wind Turbine Airfoil and Blade. International Journal of Renewable Energy Development, 6(3), 273-281.https://doi.org/10.14710/ijred.6.3.273-281